Electrically-tunable surface deformation of a soft elastomer. Issue 13 (9th March 2016) - Shian, Samuel; Clarke, David R.
Abstract : The flat surface of a thin elastomer on a conducting substrate can be deformed by applying an electric field to a percolating network of metallic nanowires randomly dispersed over the surface. Abstract : The flat surface of a thin elastomer on a conducting substrate can be deformed by applying an electric field to a percolating network of metallic nanowires randomly dispersed over the surface. The magnitude of the field-induced surface undulations increases with the applied field and can locally be several times the diameter of the nanowires. Optical imaging indicates that the effect is reversible and the surface flatness is recovered when the electric field is removed. It is found that it is the field-induced changes in the surface morphology rather than the nanowires themselves that strongly scatter light. The optical effects could be exploited in functional devices including tunable privacy windows, displays, and camouflage. There is also the potential for tuning the adhesion of elastomers to other materials.